2022
DOI: 10.1038/s41598-022-16520-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of inter-observer variation in delineation on robustness of radiomics features in non-small cell lung cancer

Abstract: Artificial intelligence and radiomics have the potential to revolutionise cancer prognostication and personalised treatment. Manual outlining of the tumour volume for extraction of radiomics features (RF) is a subjective process. This study investigates robustness of RF to inter-observer variation (IOV) in contouring in lung cancer. We utilised two public imaging datasets: ‘NSCLC-Radiomics’ and ‘NSCLC-Radiomics-Interobserver1’ (‘Interobserver’). For ‘NSCLC-Radiomics’, we created an additional set of manual con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Subsequently, this could result in undermining tumour control, as we emphasised in the current study or increasing toxicities 17,18 . Also, interobserver variability could impact the robustness of the radiomics features negatively, and the standardisation of target volume delineation could improve the stability of the prognostic value of the radiomics features 19 …”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Subsequently, this could result in undermining tumour control, as we emphasised in the current study or increasing toxicities 17,18 . Also, interobserver variability could impact the robustness of the radiomics features negatively, and the standardisation of target volume delineation could improve the stability of the prognostic value of the radiomics features 19 …”
Section: Discussionmentioning
confidence: 84%
“… 17 , 18 Also, interobserver variability could impact the robustness of the radiomics features negatively, and the standardisation of target volume delineation could improve the stability of the prognostic value of the radiomics features. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some features depend on different segmentation methods, which also affects the reproducibility and repeatability of radiomics. The traditional method is manual segmentation, which is undoubtedly time-consuming and labor-dependent, and variability between and within observers is inevitable (87). In recent years, automatic and semi-automatic segmentation techniques have been recommended to improve efficiency and reproducibility (88).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limitations, the semi-automatic tumor delineation method yielded meaningful prognostic information in our patient cohort and the benefits of using semi-automated tumor delineation on efficiency and standardization are well acknowledged in the literature. For example, previous studies showed that inter-observer variability in tumor contouring is a potential barrier to radiomic analysis of oncologic PET, and semi-automatic tumor delineation reduced the variability [ 42 , 43 ]. Each PET exam can be analyzed in as quickly as 5 min with semi-automatic tumor contouring [ 18 ], consistent with our experience in the present study.…”
Section: Discussionmentioning
confidence: 99%